The Impact of the Russian Invasion of Ukraine on the Transformation of the Liberal Discourse Regarding Freedom of Tourist Travel - Анатолій Парфіненко (Історико-політичні проблеми сучасного світу)
The war unleashed by the Kremlin regime against Ukraine has forced liberal internationalism to impose restrictions on the rights and freedoms of Russian travellers. The debate that has arisen in this regard among politicians and think tanks is the focus of this publication. The purpose of the study is to identify the transformations in the liberal policy of freedom of tourist mobility that took place during the Russian invasion of Ukraine. The methodological basis of the study is the theory of neoliberalism, public diplomacy and “soft power”. The methods of political analysis of phenomena and processes have been used. The hypothesis of the study is that the basic condition for political decision-making on visa restrictions for Russian citizens should be awareness of the ideological conflict between the mutually exclusive opposites of tourism as a positive force for peace and development and terror, the apology of which is embraced by a large part of Russian society. Accordingly, it has been concluded that the flows of Russian citizens travelling to Europe for tourism purposes pose not only a security threat as potential conductors of the ideas of the “Russian world”, but also extend moral responsibility to the host countries.